PEMBERDAYAAN SDM PETANI DAN AKSELERASI TEKNOLOGI INOVATIF MEWUJUDKAN KECUKUPAN DAN PERTAHANAN PANGAN BERDAYASAING PASCA PANDEMI COVID19 - Roosganda Elizabeth (Universitas Galuh, 2023)
Food is the most basic needs of human life. The quality and adequacy are an important role in determining the quality, the level of intelligence of human resources. The increase rice production program, in sufficient quantities and at reasonable prices remains the top priority objectives and national agricultural development. With qualitative description methods, this paper aims to review and present various levels of technology application, the level of technical efficiency, and profitability of rice farming in the various agro-ecosystems. Agriculture as nationally and regionally, still important role and occupy a strategic place and remains a major priority development policy program is contribution to Gross Domestic Product (GDP). Therefore, providing the necessary strategy and information technology as needed, the existence of adequate operational policies, support the functioning of the various institutions (research, extension, marketing), as well as government policy support a more focused and aligned to accelerate the achievement of specific technological innovation. acceleration of the application of technological innovation, improvement of national rice products and productivity, can be pursued through: increasing productivity/optimizing the potential of agricultural resources; increasing planted area and land management; support for production facilities and capital; guarantee of grain prices, selling prices and marketing of grain and rice that provide production incentives; decrease in rice consumption; improvement of management, technical, data and information; and increasing the role and capacity of related institutions. Adequate operational policy tools are needed, the functioning of various supporting institutions (research, counseling, marketing), as well as government policy support that is more focused and impartial to accelerate the achievement of location-specific technological innovations. It is necessary to evaluate agricultural development policies from the aspect of food institutions, so that strategies and efforts to accurately formulate policies in support of increasing national rice production in the future.